Pengaruh Diet Makrobiotik terhadap Penurunan Kadar Kolesterol Darah pada Penderita Penyakit Jantung Koroner - Mukti, Maria Wigianti; Saryono,; Kamaluddin, Ridlwan (Jurnal Keperawatan Soedirman, 2010)
Abnormal cholesterol level represent main risk factor incidence of Coronary Heart Desease. Diet with consuming low fat especially saturated fat and cholesterol will assist to decrease blood cholesterol high level. The macrobiotic diets is usefull to decrease blood pressure. These beneficial results, include lower blood pressure, reduced chances of getting heart disease and certain cancers that appear related to fat intake, for example breast cancer. This research aimed to know macrobiotic diets influence decrease of blood cholesterol level. The characteristic of this research are quasy experiment (pre test and post test with control group design). The sampling method was purposive sampling. T-test (with independent-samples t-test) statistical analysis was used to analyse the data. The average beginning blood cholesterol level in the case group was 216,75 mg/dl and in the control group was 216,7 mg/dl. The beginning blood cholesterol level, both group statistically did not have a significant (p = 0.998). Blood cholesterol level on day 14th in the case group was 188.8 mg/dl and in the control group was 244,85 mg/dl. The difference blood cholesterol level at both group statistically was significant (p = 0,002). It means Ho was denied and Ha was accepted. Coronary Heart Deseases patient who used macrobiotic diets had been decreasing12,9 % of their blood cholesterol level. Macrobiotic diets was influence to decrease blood cholesterol level in Coronary Heart Deseases patient at RSUD. Prof. DR. Margono Soekarjo Purwokerto.